2018
DOI: 10.1111/age.12710
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of bull fertility in US Jersey dairy cattle

Abstract: SummaryThe service sire has been recognized as an important factor affecting herd fertility in dairy cattle. Recent studies suggest that genetic factors explain part of the difference in fertility among Holstein sires. The main objective of this study was to dissect the genetic architecture of sire fertility in US Jersey cattle. The dataset included 1.5 K Jersey bulls with sire conception rate (SCR) records and 96 K single nucleotide polymorphism (SNP) markers spanning the whole genome. The analysis included w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 47 publications
2
36
0
Order By: Relevance
“…Calcium signalling is linked to a wide range of physiological and pathological processes [203][204][205], is a key driver for post-translational deimination [206][207][208] and plays an important role in the regulation of EVs [11,48]. In cattle, calcium is linked to many immunological pathways including inflammatory diseases [209], virus replication [210], parasitic infection [211], wound healing [212], reproduction [213,214] and adrenal function [215]. Interestingly, calcium regulation has been shown to differ between Holstein and Jersey cows, including via serotonergic stimulation of the calcium pathway [216].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium signalling is linked to a wide range of physiological and pathological processes [203][204][205], is a key driver for post-translational deimination [206][207][208] and plays an important role in the regulation of EVs [11,48]. In cattle, calcium is linked to many immunological pathways including inflammatory diseases [209], virus replication [210], parasitic infection [211], wound healing [212], reproduction [213,214] and adrenal function [215]. Interestingly, calcium regulation has been shown to differ between Holstein and Jersey cows, including via serotonergic stimulation of the calcium pathway [216].…”
Section: Discussionmentioning
confidence: 99%
“…Gene ontology terms can be defined as groups of genes that are involved in the same biological process or molecular function. In our previous studies, using Fisher's exact test, we identified 2 GO terms, namely calcium ion binding (GO: 0005509) and pyrophosphatase activity (GO: 0016462), significantly enriched with genes associated with SCR in both Jersey and Holstein breeds (Peñagaricano et al, 2013;Rezende et al, 2018). Here, we assessed the set of SNP linked to genes in these 2 relevant GO terms.…”
Section: Alternative Snp Subsetsmentioning
confidence: 99%
“…The US dairy industry has had access to a phenotypic evaluation of dairy bull fertility called sire conception rate (SCR) that is based on a large, nationwide database of confirmed pregnancy records . Notably, there is a remarkable variation in SCR with more than 10% conception rate difference between high-fertility and low-fertility bulls (Peñagaricano et al, 2012;Rezende et al, 2018). Therefore, it is clear that service sire fertility should be considered in breeding schemes aimed to improve the reproductive efficiency of dairy herds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some fatty acids present crucial role in the maintenance of sperm integrity, sperm motility, viability and fertility in several livestock species (Van Tran, Malla, Kumar, & Tyagi, ). Rezende, Dietsch, and Peñagaricano () found some genes associated with sire conception rate that were enriched in a functional term named “Fatty acid degradation” and reported previous studies that explained the relationship between fatty acids and the ATP synthesis, promoting the sperm motility (Amaral et al, ).…”
Section: Discussionmentioning
confidence: 92%